Meiobenthic Invertebrates Community Associated with Aquatic plant Ceratophyllum demersum Salamiyat irrigation canal / north Baghdad - Baghdad Science Journal (مجلة بغداد للعلوم, 2017)
The aim of the present study is to study the meiobenthic invertebrate's community associated with the aquatic plant Ceratophyllum demersum in Al-Salamiyat irrigation canal / north Baghdad, with the chemical and physical parameters of the canal water, during the study period from September 2015 to May 2016. Two sites were chosen for sample collection, the first site (S1) at the beginning of the canal near it's connection with Tigris river, and the second site (S2) after 10 km from the first site. The chemico-physical analysis results revealed that the water temperature ranged from 10-30oC, and pH values ranged between 6.9-7.8, and the dissolved oxygen concentration and the BOD values from 7.2-9.2 mg/l, and 1.2-5.4 mg/l, respectively. The salinity values were ranged between 0.45 and 0.86 ‰, and the total suspended solids were changed 357-674mg/l. A total of 9089 individuals of meiobethic invertebrates were sorted out from C. demersum during the study perid , representing 34 species including Hydra oligactis (Hydrozoa , Cnidaria); two species of Turbellaria ( Platyhelminthes); five species of Nematoda; seven species of Rotifera; 14 species of aquatic Oligochaeta (Annelida); four Crustacea, and one species of chironomid larva species, in addition to recording one individual of Tardigrada from (S2). The highest total number of meiobenthic invertebrates of 5600 individuals were recorded at (S2), while at (S1) less number of (3489) individuals were reported. Four species were recognized as a new records for Iraqi fauna, including Hydra oligactis (Hydrozoa:Cnidaria); Macrostomum tuba (Platyhelminthes: Turbellaria(, Dero cooperi (Annelida:Oligochaeta,) and Stenocypris hislopi )Crustacea: Otracoda(.